Comparative studies of flow cryptographic transformation algorithms - Kuznetsov О.О.; Ivanenko, D.V.; Lutsenko, M.S.; Timchenko, V.A.; Melkozerova, O.M.; Osadchuk, M.O.; Ostryanska, Ye.V. (Radiotekhnika, 2017)
The main results of comparative studies of flow cryptographic transformation algorithms are described, in particular those ones standardized in ISO / IEC 18033-4, ISO / IEC 29192-3 and presented as winners of international projects eSTREAM and CRYPTREC. Comparative studies were carried out in two directions: first, statistical safety was investigated by testing the output sequences; secondly, the speed of the generators in certain modes of practical application was evaluated. The most promising areas of further research on the development and application of a new flow cipher in Ukraine are justified.